PENGARUH ENTERPRISE RISK MANAGEMENT TERHADAP NILAI PERUSAHAAN DENGAN CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI - Lina; Shantika Manggala (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2025)
This study aims to provide empirical evidence regarding the influence of enterprise risk management on firm value. In addition, this study aims to investigate the moderating role of corporate governance mechanisms, specifically independent commissioners, audit committees, and boards of directors, in enhancing the impact of enterprise risk management on firm value. This study uses 624 data from manufacturing sector companies listed on the Indonesia Stock Exchange for the 2019-2022 period. Hypothesis testing uses multiple regression analysis and moderated regression analysis methods. This study reveals that enterprise risk management has a positive influence on firm value. Meanwhile, independent commissioners, audit committees, and boards of directors as corporate governance mechanisms have not been proven to be able to strengthen the influence of enterprise risk management on company value.